Implementasi sistem manajemen keselamatan dan kesehatan kerja di Pt. Pln (Persero) Rayon Rote Ndao - Tudermi Maksimilyan Fioh; Anderias Umbu Roga; Johny A. R. Salmun; Franky M. S. Telupere (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2021)
The determining or the implementation of occupational safety and health management system is an obligation for all companies as is already mandated in Government Regulation Number 50 in 2012. The implementation have an aim to reduce the risk level of work accident noraltough the occupational illness which may be happening in work environment. The aim of this research is to cover the implementation of occupational safety and health management system at PT. PLN (Persero) Rayon Rote Ndao. This research is using descriptive analysis method with total five informants which are consist of the manager of PT.PLN (Persero) Rayon Rote Ndao, supervisor K3, office employee, field employee and engineer. The research result shows that theoccupational safety and health management system’s commitment and the policy, the occupational safety and health management system’s planning, the occupational safety and health management system’s implementation, the occupational safety and health management system’s measurement and evaluation, and the occupational safety and health management system’s review and improvement in PT.PLN (Persero) Rayon Rote Ndao have already been well applyed.